2013
DOI: 10.1111/age.12050
|View full text |Cite
|
Sign up to set email alerts
|

Investigating gene expression differences in two chicken groups with variable propensity to feather pecking

Abstract: Feather pecking is a major welfare problem in egg production. It may be caused by genetic, physiological and environmental factors. The main aim of this study was to uncover gene expression variability in brain tissue between individuals from high feather pecking and low feather pecking groups using the Chicken Gene Expression Microarray. In total, 313 signals were initially identified as significant (P ≤ 0.05) for the fold change higher than two. A subset of functional candidate genes including downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…However, this relation between feather eating and increased peripheral 5-HT remains speculative and further research is needed. Based on our findings we suggest that divergent selection on FP affects whole blood 5-HT, potentially via mutations and/or alterations in expression of genes involved in the serotonergic system as previously found in relation to feather damage [20] and in the FP selection lines [54,55]. This is supported by the finding that whole blood 5-HT level was consistent between ages in the HFP line, but not in the CON and LFP lines.…”
Section: Serotonergic Systemsupporting
confidence: 87%
“…However, this relation between feather eating and increased peripheral 5-HT remains speculative and further research is needed. Based on our findings we suggest that divergent selection on FP affects whole blood 5-HT, potentially via mutations and/or alterations in expression of genes involved in the serotonergic system as previously found in relation to feather damage [20] and in the FP selection lines [54,55]. This is supported by the finding that whole blood 5-HT level was consistent between ages in the HFP line, but not in the CON and LFP lines.…”
Section: Serotonergic Systemsupporting
confidence: 87%
“…Molecular analyses suggested putative candidate genes for feather pecking behaviour [ 29 31 ]. According to Keeling et al [ 29 ], the PMEL 17 ( premelanosome protein ) gene affects plumage melanisation and the amount of feather pecking received.…”
Section: Discussionmentioning
confidence: 99%
“…Two other candidate genes, dopamine receptor D4 ( DRD4 ) and DEAF1 transcription factor ( DEAF1 ), have been shown to be associated with FP behaviour [ 30 ]. Gene expression analyses with brain tissues collected from individuals of the same HFP and LFP lines as those used here have led to the identification of six candidate genes, namely HTR1B ( 5 - hydroxytryptamine ( serotonin ) receptor 1B, G protein - coupled ), SIP1 ( Smad interacting protein 1 ), PSEN1 ( presenilin - 1 ), GLUL ( glutamate - ammonia ligase ), TSPO ( translocator protein ) and MAOA (monoamine oxidase A ), which may be involved in FP behaviour [ 31 ]. However, none of these candidate genes were located in the 13 cluster regions identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study by van Hierden et al [ 58 ] demonstrated that lines of chicken divergently selected for their feather pecking propensity showed a different serotonin turnover with a slower degradation of serotonin in the HFP (High Feather Pecking) than in the LFP lines (Low Feather Pecking). Moreover, Wysocki et al [ 59 ] studied MAOA expression in brain tissue of HFP and LFP lines and suggested that it could possibly be downgraded in HFP. However, the observation on micro-arrays could not be confirmed by qPCR.…”
Section: Discussionmentioning
confidence: 99%